Educating for the Environment: The Role of the Host Destination in Education Travel Programs - Brack W. Hale (Sustainability, 2021)
The benefits from educational travel programs (ETPs) for students have been well-documented in the literature, particularly for programs looking at sustainability and environmental issues. However, the impacts the ETPs have on the destinations that host them have been less frequently considered; most of these studies focus, understandably, on destinations in the Global South. This paper draws on a framework of sustainable educational travel to examine how ETPs affect their host destinations in two case study destinations, based on the author’s professional experience in these locations, interviews with host organizations that use the lens of the pandemic, and information from government databases. The findings highlight an awareness of the sustainability of the destination, the importance of good, local partnerships with organizations well-connected in their communities, and educational activities that can benefit both students and hosts. Nonetheless, we have a long way to go to understand the full impacts of ETPs on their host destinations and thus truly learn to avoid them.